2019
DOI: 10.1038/s41598-019-46807-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic and pituitary transcriptome profiling using RNA-sequencing in high-yielding and low-yielding laying hens

Abstract: The reproductive physiology and laying performance of laying hens are regulated by the hypothalamus and pituitary. To understand the mechanism of egg laying regulation, we sequenced and analysed the hypothalamus and pituitary expression profiles in high- and low-yielding laying Chinese Dagu Chickens (CDC) using RNA-seq. More than 46 million clean reads and 24,873 tentative genes were obtained using the Gallus gallus genome as a reference. Transcriptome analysis in hypothalamus and pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…In this process, the hypothalamus produces gonadotropin-releasing hormone-I (GnRH-I) which triggers pituitary gland (adenohypophysis) to release FSH and LH, and stimulates the secretion of estradiol (E2) and progesterone (P4) in ovary while ovulation 19 . Hitherto, several studies have focused to uncover the molecular mechanism associated with egg production performance in chicken 10,20,21 . However, the differential gene expression and key pathways mediating the egg production process across hypothalamic-pituitary-ovarian (HPO) axis are yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, the hypothalamus produces gonadotropin-releasing hormone-I (GnRH-I) which triggers pituitary gland (adenohypophysis) to release FSH and LH, and stimulates the secretion of estradiol (E2) and progesterone (P4) in ovary while ovulation 19 . Hitherto, several studies have focused to uncover the molecular mechanism associated with egg production performance in chicken 10,20,21 . However, the differential gene expression and key pathways mediating the egg production process across hypothalamic-pituitary-ovarian (HPO) axis are yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…In down-regulated DEGs, significant GO terms for biological processes were response to lipid catabolic process phospholipid metabolic process, embryonic organ development, and response to extracellular stimulus. Due to the smaller number of DEGs (10) identified in thalamus tissue between HEP versus LEP chicken group, the GO term could not be assigned.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…This insular approach has led to an inevitable bottleneck where data on cellular and biochemical processes within specific cell types or nuclei have multiplied without a clear/tangible link to physiological function. Similarly, recent efforts in single-cell transcriptomics of the hypothalamus ( Romanov et al 2017 , Wang & Ma 2019 ) have documented a highly complex heterogenous hypothalamus, but the implication of neuropeptide expression for physiological function remains difficult to interpret without appropriate tools. Nevertheless, technological developments in genetics and systems neuroscience have enabled specific neurons to be manipulated in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…PRL is generally considered to be a key factor in the onset and maintenance of broody behaviour in birds, and it has been well established that the elevated plasma PRL inhibits gonadotropin release, ovum development and ovulation, resulting poor laying performance and even complete cessation of egg production in laying hens [59][60][61][62]. Transcriptome studies have also revealed PRL is associated with egg production performance in chicken hypothalamic-pituitary-ovarian axis [63,64]. Therefore, the signi cant difference in eggshell quality (EST, ESS, eggshell weight, and cuticle opacity) and egg production performance between GC and PC group hens may be related to the different expression patterns of PRLR gene in the uterus.…”
Section: Discussionmentioning
confidence: 99%